Differentiated discharge patterns, causes and prevention measures of rural non-point source pollution in the four economic regions of mainland China. (February 2023) - Wang, Yongsheng; Cui, Xiao; Zou, Lilin; Wen, Qi
Abstract: Agricultural non-point source pollution has got more attention than rural non-point source pollution (RNPSP) in the past decades. Discharge patterns, causes and prevention measures of RNPSP in the four economic regions of mainland China are still lacking. Based on the framework for RNPSP assessment from agricultural production and rural resident living, inventory analysis and redundancy analysis methods were used to calculate the discharges of RNPSP and identify its influence factors, respectively. During 1978–2019, increased national per capita chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) discharges with values of 1.62, 3.04 and 3.86 times was found, respectively. Northeast and eastern regions always had the higher per capita COD, TN and TP discharges than those of national average. In addition, eastern region had highest average per capita discharges of COD, TN and TP with increased times of 1.90, 2.67 and 2.47 than the national average. The biggest variations of per capita discharges of COD, TN and TP were mainly occurred in Shandong, Liaoning and Fujian provinces from eastern region, and in Inner Mongolia from western region. Livestock and poultry were the dominate sources of per capita COD and TP discharges, while contribution of fertilization was highest to per capita TN discharge. Agricultural production had higher contribution to the national per capita COD, TN and TP discharges with ratios of 75.56%, 90.27% and 82.51%, respectively. Highest contribution of agricultural production in northeast region and rural resident living in western region should be noted. Redundancy analysis shows that pig was the key factor of RNPSP discharges in the four economic regions. Freshwater aquaculture and resident living were the important factors to RNPSP discharges in northeast and eastern regions, respectively, while rice planting should be highlighted to the discharges of RNPSP in central and western regions. Our results revealed the different discharge patterns and causes of RNPSP in the four economic regions of mainland China. The increased RNPSP discharges were associated with intensified agricultural production which was driven by changed resident lifestyles. Targeted RNPSP controlling strategies should be carried out besides the universal and important strategies involving fertilization, and livestock and poultry in four economic regions. Highlights: An inventory analysis method was used to calculate the discharges of rural non-point source pollution (RNPSP). Fertilization, livestock and poultry were the dominate sources of per capita RNPSP discharges. Increased RNPSP discharges were associated with intensified agricultural production which was driven by changed resident lifestyles. Targeted RNPSP controlling strategies should be carried out in four economic regions.